Some epidemiological aspects of the outbreak of Japanese encephalitis in Anuradhapura District, Sri Lanka, 1985-86 - Abeysinghe, M.R.N (My University, 1987)
Epidemiological findings of the first major outbreak of Japanese encephalitis which occurred between November,1985 and February,1986, in Anuradhapura and the surrounding districts are presented. Out of the 326 cases,120 cases were serologically confirmed. The case fatality rate was 19.9 per cent. The incidence rate was 45.6 per 100,000 population and the mortality rate was 7.9 per 100,000 population. There had been 326 cases of Japanese encephalitis patients admitted to the general hospital, Anuradhapura, out of which 120 were serologically confirmed. There were 65 deaths showing a case fatality rate of 19.9 per cent. The incidence rate for Anuradhapura district was 45.6 per 100,000 population and the mortality rate was 7.9 per 100,000 population. The sex specific incidence rate was higher among males.75 per cent increase in the extent of area under paddy cultivation 25 per cent increase in the Mahaweli H area,10-fold increase in pig breeding and high rain fall immediately prior to and during this period, facilitated the breeding of mosquito vectors led to the occurrence of this outbreak. In view of this situation, it is necessary to consider the systemization of the whole paddy cultivation structure so as to minimize mosquito breeding, introduction of new crops and techniques, effective water management, introduction of larvivouras fish use of correctly identified insecticides. The true role of the domestic animal in the transmission of Japanese encephalitis virus in this country is to be identified and it needs further research. The correct target population has to be identified before any such immunization is considered. It would be necessary to educate the people in regard to the disease